CONSUMER PROTECTION IN THE PURCHASE OF RECONDITIONED ELECTRONIC GOODS IN BANDA ACEH: An analysis of Islamic law and Law No. 8 of 1999 on Consumer Protection - M. Farhan (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2025)
This study aims to analyse legal protection for consumers in the purchase of reconditioned electronic goods in Banda Aceh, viewed from the perspective of Islamic law and Law No. 8 of 1999 on Consumer Protection. The research method employed is a qualitative approach, utilising data collection techniques that include literature reviews, field observations, and interviews with consumers and business actors. The results of the study indicate that many business operators use ambiguous terms, such as